Alternative Legal Strategies and Ninik Mamak Authority: Dual Administration of Malay Marriage in Koto Kampar Hulu, Riau - Mustafid Mustafid; Kemas Muhammad Gemilang; Firman Surya Putra; Azzuhri Al Bajuri; Mawardi Mawardi (Journal of Islamic Law)
The regulation of marriage registration in several Muslim countries tends to emphasize administrative aspects rather than substantive ones. For the Malay customary community in Koto Kampar Hulu, Riau, Indonesia, their obligations are not only limited to fulfilling marriage administration under state law but also involve obtaining permission from ninik mamak (traditional leader). Therefore, this article aims to analyze marriage administration in the context of customary law and state law within the Malay customary community, as well as to reveal alternative legal strategies they employ to circumvent traditional marriage administration. Field research was conducted through interviews with 16 key informants and direct observation of the completeness of marriage administration. The results show that the Malay customary community must navigate dual marriage administrations—customary law and state law—to obtain the legality of marriage before the state. Permission from ninik mamak serves as the basis for acquiring documents from the village head, fulfilling the administrative requirements for marriage registration at the local religious affairs office. The authority of ninik mamak in granting marriage permission aims to resolve conflicts and customary obligations before marriage while preserving the identity and traditions of the customary community. For those who disregard customary administration, they adopt alternative legal strategies such as unregistered marriages (nikah sirri) or relocating to another village. The alignment between customary law and state law is reflected in this study, particularly in the context of marriage registration.